Effects of Genotype and Climatic Conditions on the Oil Content and Its Fatty Acids Composition of Carthamus tinctorius L. Seeds - Kamel Zemour; Ahmed Adda; Amina Labdelli; Abdelkader Dellal; Muriel Cerny; Othmane Merah (Agronomy, 2021)
Safflower seeds provide an oil rich in mono and polyunsaturated fatty acids. Its adaptation to drought and high temperatures makes it an alternative for the development of oleaginous crops in semi-arid areas. This study examines the oil content and the chemical composition of seed oil from three safflower accessions (Gila, Halab, Touggourt) cultivated over three years (2015, 2016 and 2017) in a semi-arid area in Tiaret (West of Algeria). Under these semi-arid conditions, characterized by low rainfall and high temperatures, seed oil content remained relatively high and was composed mainly of unsaturated fatty acids, with their ratio to saturated fatty acids reaching an average value of 9. Seed oil content varies between 22.8% and 28.4% among the genotypes and throughout the three years. The extracted oil consists essentially of unsaturated fatty acids, linoleic and oleic acids, poly and monounsaturated, respectively. Their contents over the three years vary between 75% and 79.3% for linoleic acid and between 10.2% and 14.7% for oleic acid. The saturated fatty acids content of the oil reached a maximum value of 9%. They consist mainly of palmitic acid, of which the average genotypic content varies between 6.6% and 7.15% depending on all grown years. The results obtained may assist in better understanding the response of cultivars under rainfed conditions and could be helpful for breeders with regards to introduction into selection programs.